Cattle productivity and diet in northern Nigeria - Milligan, K. (International Livestock Centre for Africa, 1979)
Summarizes available published information on the productivity & diet of White Fulani (Bunaji) cattle in northern Nigeria, with particular reference to growth, reproductive performance & milk yields of animals, and types, production and utilization of forage.